Holding sacred ground : - Glickman, Carl D. (Jossey-Bass, 2003)
Glickman (education, Southwest Texas State University) draws on his experience as director of a school improvement program dealing with some 100 diverse K-12 schools. He offers advice on leadership formats that support truly democratic education, and provides examples of curriculum and methods for improving achievement and building citizenship capabilities.